2022
DOI: 10.32938/sc.v7i01.1712
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Arang Sekam dan Pupuk Kotoran Ayam terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.)

Abstract: Penelitian ini bertujuan untuk (1) mengetahui pengaruh pemberian arang sekam terhadap pertumbuhan dan hasil sawi hijau, (2) mengetahui pengaruh pemberian pupuk kotoran ayam terhadap pertumbuhan dan hasil sawi hijau, (3) mengetahui interaksi perlakuan pemberian arang sekam dan dosis pupuk kotoran ayam terhadap pertumbuhan dan hasil sawi hijau. Penelitian ini dilaksanakan pada September 2019 sampai dengan Januari 2020 di Screen House Fakultas Pertanian Universitas Jenderal Soedirman. Rancangan percobaan yang dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…One of the most frequently used soil amendments is rice husk charcoal. Charcoal husks are often used by farmers to improve agricultural land (Yoedhistira & Darmawan, 2022). In addition, there have been many studies using rice husk charcoal for mixed media and its effect on plant growth (Mishra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequently used soil amendments is rice husk charcoal. Charcoal husks are often used by farmers to improve agricultural land (Yoedhistira & Darmawan, 2022). In addition, there have been many studies using rice husk charcoal for mixed media and its effect on plant growth (Mishra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One type of livestock manure that has the potential to become a useful organic material is chicken manure which in general has not been utilized optimally by the community, even though according to several research results, it has been found that chicken manure waste contains high enough organic matter so that it can be reapplied to plants as fertilizer (Dani et al, 2021). Chicken manure contains complete nutrients needed by plants for growth such as essential nutrient (Yoedhistira & Darmawan, 2022). This study aims to determine the effect of LOF dose and plant media on enhancing the growth and the production of spinach.…”
Section: Introductionmentioning
confidence: 99%